"WANT TO BE ALL FINLAND". SIDE EFFECTS OF PISA - Javier Barquín Ruiz; Monsalud Gallardo Gil; Manuel Fernández Navas; Rafael Yus Ramos; Mª Pilar Sepúlveda Ruiz; Mª José Serván Núñez (Ediciones Universidad de Salamanca, 2011)
This article describes some of the considerations on the PISA (Program for International Student Assessment) of the OECD, have been reviewed by the Research Group HUM-311, University of Malaga in the Project R & D-SEJ 2007-66967, led by Professor D. Angel I. Pérez Gómez. In developing this review, addressed the issue of basic skills as a potential mechanism for the development of useful life skills of individuals in the knowledge society, second-order powers specifically listed in the generic construct Learn how to Learn. Addressing these analysis, questioning the most problematic aspects.